Pisma SKS i niezależnego ruchu studenckiego 1977-1980 - Kuta, Cecylia (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2023)
Established in the second half of the 1970s, the Student Solidarity Committees (Studenckie Komitety Solidarności, SKS) were the first student organisation openly active in government opposition. Their activists organised educational campaigns, seminars aimed at familiarising students with history and literature that were absent from school curricula, collected signatures for petitions defending the oppressed, took part in protests and organised training camps. Publishing was an important form of activity for the SKS and the Independent Students’ Association. Periodicals published by those circles had a significant impact on the development of the second circulation. This issue is the main focus of this paper. It discusses and compares the publishing activity of the bodies within which the Student Solidarity Committees functioned.